2016
DOI: 10.1016/j.gca.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Does crystallographic anisotropy prevent the conventional treatment of aqueous mineral reactivity? A case study based on K-feldspar dissolution kinetics

Abstract: 18Which conceptual framework should be preferred to develop mineral dissolution rate 19 laws, and how the aqueous mineral reactivity should be measured? For over 30 years, the 20 classical strategy to model solid dissolution over large space and time scales has relied on so-21 called kinetic rate laws derived from powder dissolution experiments. In the present study, we 22 provide detailed investigations of the dissolution kinetics of K-feldspar as a function of 23 surface orientation and chemical affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 62 publications
8
47
1
Order By: Relevance
“…On the whole, orientation seems to be the only passivated orientation in an undersaturated fluid, while was the only non-passivated orientation amongst those tested in a saturated fluid. Consistent with the mechanism leading to passivation proposed above, the the fact that the face is among the slowest dissolving faces of feldspars (Zhang and Lüttge, 2009;Pollet-Villard et al, 2016) may explain why it was the sole face that was systematically passivated at pH 2.5.…”
Section: Internal Interfacesupporting
confidence: 55%
“…On the whole, orientation seems to be the only passivated orientation in an undersaturated fluid, while was the only non-passivated orientation amongst those tested in a saturated fluid. Consistent with the mechanism leading to passivation proposed above, the the fact that the face is among the slowest dissolving faces of feldspars (Zhang and Lüttge, 2009;Pollet-Villard et al, 2016) may explain why it was the sole face that was systematically passivated at pH 2.5.…”
Section: Internal Interfacesupporting
confidence: 55%
“…First, as noted in section 3.4 below, the surface area normalized dissolution rate of a mineral can depend strongly on its crystallographic orientation (cf. Bandstra and Brantley, 2008;Daval et al, 2013;Pollet-Villard et al, 2016). This undermines the accuracy of using a single surface area to quantify the rates of a mineral grain consisting of numerous different crystallographic faces, in part as the relative proportion of each surface can change during the dissolution of the mineral.…”
Section: Effect Of Surface Areamentioning
confidence: 99%
“…For example, from K-feldspar surface rate measurements, Pollet-Villard et al [34] found that despite increased etch pit distribution, surface retreat was a linear function of time. Furthermore, these authors reached the conclusion that anisotropic mineral reactivity lead to a continuous modification of the dissolution rate as a function of reaction time.…”
Section: On Temporal Rate Variabilitymentioning
confidence: 99%
“…Furthermore, these authors reached the conclusion that anisotropic mineral reactivity lead to a continuous modification of the dissolution rate as a function of reaction time. Pollet-Villard et al [34] also concluded that because of a significant variation in (intrinsic) surface reactivity, it was inappropriate to use the "mean rate" approach to quantify the reactivity of crystalline materials. In contrast, some researchers have reported an intrinsic decrease of long-term dissolution rate of the considered surface due to the development of pit walls with lower surface energy [35,36].…”
Section: On Temporal Rate Variabilitymentioning
confidence: 99%